THE RELATIONSHIP BETWEEN POLITICAL BUDGET TRANSPARENCY AND PUBLIC TRUST: A THEORETICAL REVIEW AND EMPIRICAL EVIDENCE - Melyana R Pugu; Loso Judijanto (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study examines the relationship between political budget transparency and public trust through a theoretical review and empirical evidence. Transparency in political budget management is shown to play a crucial role in building and maintaining public trust. Trust theory indicates that greater access to information and openness in budget practices enhances public perceptions of the integrity and accountability of political actors. Empirical evidence from various countries shows a positive correlation between levels of budget transparency and levels of public trust. Countries with more transparent budget practices tend to have higher public trust indices. However, budget transparency alone is not enough; responsiveness and accountability in responding to public input and criticism are also needed to strengthen public trust. Therefore, this study concludes that budget transparency should be implemented as part of a holistic approach that includes responsiveness and public participation to achieve effective governance and build sustainable public trust.